CrAlSiN barrier layer to improve the thermal stability of W/CrAlSiNx/ CrAlSiOyNx/SiAlOx solar thermal absorber - Al-Rjoub, A. (2019)
The influence of adding CrAlSiN barrier layer between the back-reflector tungsten (W) and stainless-steel substrate on thermal stability has been investigated. In previous work, after the annealing in vacuum at 600 ºC, tungsten diffusion from the back-reflection layer towards the stainless-steel substrate was found. In this study, a barrier layer was added and its influence upon the W diffusion was studied. Several designs of multilayer solar selective absorber for high temperature applications were used to test the thermal and chemical stability and oxidation resistance after vacuum annealing. These samples were characterized by Scanning Electron Microscopy (SEM), Rutherford Backscattering Spectrometry (RBS), X-ray diffraction (XRD), Fourier-transform Infrared Spectroscopy (FTIR) and UV–VIS–NIR spectroscopy. All absorber tandems show good thermal stability after vacuum annealing at 600 ºC and the changes in optical constants solar absorptance (α) and thermal emittance (ε) are negligible. In some cases, small changes in the reflectance curves after the first step of annealing were seen. Some changes were found in the oxide layer, due to the incomplete oxidized Si atoms, as confirmed by FTIR analyses. This cannot justify the increase of NIR reflectance observed in the optical stacks after annealing, which can be due to the phase changes of the back-reflector tungsten layer. All layers of stacks are amorphous, except the tungsten layer, which is polycrystalline and shows a columnar growth. The addition of a CrAlSiNP= 0.11 Pa barrier layer between tungsten and stainless-steel substrate proved to be a good solution to control the diffusion of W atoms towards the substrate, whereas using higher nitrogen partial pressure in the high and the low absorption layers reduce the diffusion of Cr from those layers to surface.